PENDAMPINGAN PENGELOLAAN INSTAGRAM SEBAGAI MEDIA KOMUNIKASI PEMASARAN UMKM GIPANG IKE-KE CILEGON - Widya Nur Bhakti Pertiwi; Ghina Nur Aini; Khaila Priwisastra; Nabila Audy (Indonesian Collaboration Journal of Community Services, 2023)
SMEs Gipang Cassava IKA-KE has been around since 2013, located in the Cilentrang RT. 02/01 No. 126 Purwakarta Village, Purwakarta District, Cilegon. Mrs. Djum'ati as the owner of the IKA-KE Gipang Cassava UMKM said that the background for the establishment of this business was from a friend's request. The response from the first sales was good, Mrs. Djum'ati expanded her business, and started selling the cassava gipang at the puskesmas, village office, and several cooperatives in Krakatau Steel's subsidiary. In 2015 Gipang Cassava IKA-KE won 2nd place in the Banten Province food innovation championship. Already having a turnover of IDR 10,000,000 per month, Gipang Cassava IKA-KE only sells its products around Cilegon and Serang. Gipang Cassava IKA-KE has not succeeded in entering markets outside the two cities. The Covid-19 pandemic in 2020-2021, caused IKA_KE's Gipang Cassava sales turnover to decrease by more than 50%. This is because IKA-KE's Gipang Cassava only sells through conventional channels, which during the Covid-19 pandemic limited their operating hours, such as cooperatives and village offices. The method of implementing this community service activity includes preparation, implementation of assistance, as well as evaluation and monitoring. The results of this dedication show positive results. UMKM Gipang Cassava IKA-KE has a social media with 109 followers, which has succeeded in increasing sales by 40%, and also expanding the market to Jakarta and West Java